Odpowiedź:
Mamy
[tex]t_1 + t_2 =2 t[/tex]
[tex]\frac{S}{v + 1,5}[/tex] + [tex]\frac{S}{v - 1} = 2*\frac{S}{v}[/tex] / : S
[tex]\frac{1}{v + 1,5}[/tex] + [tex]\frac{1}{v - 1}[/tex] = [tex]\frac{2}{v}[/tex]
[tex]\frac{v - 1 + v + 1,5}{(v + 1,5)*( v - 1)}[/tex] [tex]= \frac{2}{v}[/tex]
( 2 v + 0,5)*v = 2*( v² - v + 1, 5 v - 1, 5)
2 v² + 0,5 v = 2 v² + v - 3
0,5 v - v = - 3
- 0,5 v = - 3 / * ( - 2)
v = 6
Odp. Turysta szedł ze średnią prędkością v = 6 km/h.
=================================================
Szczegółowe wyjaśnienie: